METHODOLOGY AND OUTCOMES OF ENGLISH LANGUAGE TEACHING (Scientific journal of the Fergana State University, 2025)
This paper examines the methodologies employed in English language teaching (ELT) and their impact on learner outcomes. It explores various pedagogical approaches, including communicative language teaching (CLT), grammar-translation, task-based learning, and technology-integrated methods, analyzing their effectiveness in developing different aspects of language proficiency (reading, writing, listening, and speaking). The study considers the influence of learner characteristics (e.g., learning styles, motivation, prior language experience) and contextual factors (e.g., teacher training, resource availability) on the success of different ELT methodologies. By reviewing existing research and identifying best practices, the paper aims to provide insights for educators and policymakers seeking to optimize ELT methodologies to achieve improved learner outcomes and enhance overall language proficiency.